2011
DOI: 10.1108/20426781111146754
|View full text |Cite
|
Sign up to set email alerts
|

Does order matter? An empirical analysis of NHL draft decisions

Abstract: Purpose -The purpose of this paper is to examine the effect of order on the quality of outcomes when making sequential decisions and test the widely-held belief that choosing earlier is preferable and results in better outcomes than choosing later. Design/methodology/approach -Quantitative performance from the sequence of athletic decisions made by the teams of the National Hockey League (NHL) at the annual amateur entry draft is longitudinally analyzed using a participation threshold of 160 games. Findings -A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Many of the critiques of team drafting are that for a given selection a player whose future performance exceeded the current selection was often available. See, for example, Tingling (2011). Given the difficulty with projecting the future performance, it is important to focus on the trends rather than individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the critiques of team drafting are that for a given selection a player whose future performance exceeded the current selection was often available. See, for example, Tingling (2011). Given the difficulty with projecting the future performance, it is important to focus on the trends rather than individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Tingling et al (2011) show that NHL players chosen in the first turn and in the first half of the second turn of the ED are indeed significantly more successful, so choosing earlier rather than later is important for the first two turns. A related study by Berri (2008) for a similar tournament system (NBA) points out that the first draft pick is the best choice.…”
Section: Are There Incentives To Lose?mentioning
confidence: 87%
“…Tingling et al (2011) found evidence that the new eligible high quality NHL players were indeed signed by the worst teams. Moreover, Grier and Tollison (1994) presented some empirical evidence that EDs in professional football promote competitive balance and Maxcy (2002) argued that competitive balance also improved with the implementation of the ED in the Major League Baseball.…”
Section: General Information On Entry Draftsmentioning
confidence: 99%
“…Researchers mostly analyze the structure as well as the decision‐making within the process or look for inefficiencies from an economic standpoint. Papers on the draft can be found for the NHL (e.g., Deaner et al, 2013; Tingling et al, 2011), the MLB (e.g., Caporale & Collier, 2013; Sims & Addona, 2016), the NFL (e.g., Hendricks et al, 2003; Massey & Thaler, 2013), and the WNBA (e.g., Harris & Berri, 2015; Hendrick, 2016).…”
Section: Background Related Literature and Modelsmentioning
confidence: 99%